TRANSPLANTATION OF GIANT GOURAMY (Osphronemus gouramy) TESTICULAR CELLS IN EARLY HATCHING TILAPIA (Oreochromis niloticus) LARVAE - Jasmadi Jasmadi; Odang Carman; Alimuddin Alimuddin (Widyariset, 2016)
Cell transplantation technology has been widely developed in mammals, but less implemented in inland aquaculture fish. Giant gouramy (Osphronemus gouramy) is one of important comercial aquaculture commodities that has a relatively long first reproductive cycle compared to the tilapia (Oreochromis niloticus).  Tilapia  has  a  faster  reproductive cycle  and  potential  as  giant gouramy surrogate broodstock. This study was aimed to applicate testicular cell transplantation technology of giant gouramy in tilapia larvae and to evaluate  its  success  rate  trough  donor cell  colonization.  Tilapia  larvae  of 1-2 dph (days post hatching) and 3-4 dph were injected with ±20.000 giant gouramy testicular cells in the peritoneal cavity, and then groomed for two months. Cell colonization of spermatogonium donor was determined by Polymerase Chain Reaction (PCR), using giant gouramy F1-Growth Hormone and R1-Growth Hormone primers. The result of cell dissociation showed that a  bigger  giant gouramy  (827  g)  had  lower  of  spermatogonia  composition (4.45%) than a smaller gouramy (608 g) (14.96%). Donor cell colonization in  1-2 dph  recipient  was  higher  (100%)  than  in  3-4  dph  recipient  (75%). Whereas recipient Survival Rate (SR) was 89.34% for 1-2 dph recipient and 98.96% for 3-4 dph recipient respectively. This study suggests that testicular cell transplantation technology of giant gouramy could be appllied to tilapia (Xenotransplantation)  and  cell  transplantation  has  a better  performance in  1-2  dph  than  in  3-4  dph  recipients.  With such  success,  there  is  a  high potential that the giant gouramy cultivation can be increased through the cell transplantation technology.